(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2026)
The purpose of this study is to determine the extent of the influence of organizational culture variables on employee performance variables at the Department of Agriculture in Pangkep Regency. The method used in this research is a quantitative approach with descriptive research type. Data collection techniques were carried out through surveys using Likert-scale questionnaires distributed to 90 employees as samples through a saturated sampling technique. Data analysis was performed by assessing respondents’ responses to the level of organizational culture and employee performance, and using multiple linear regression analysis to identify the relationship between the two variables. he results of this study indicate that the organizational culture variable is categorized as ’Excellent,’ with an average score of 407.6 or a percentage of 90.57%. Similarly, the employee performance variable falls into the ’Very High’ category, yielding an average score of 404.5 or 89.88%. Furthermore, multiple linear regression analysis demonstrates that organizational culture has a positive and significant effect on employee performance, with a coefficient of determination of 0.681, or 68.1%